ANALYTICAL INSPECTION AND DEVELOPMENT OF A CLASSIFICATION OF NEEDLE THREADS TEKE-UP MECHANISMS OF CHAIN STITCH SEWING MACHINES - МАНОЙЛЕНКО, О. П.; ГОРОБЕЦЬ, В. А.; ДВОРЖАК, В. М.; ПИСАРЕНКО, Д. Д.; БИЛИК, К. А. (Technologies and Engineering, 2023)
Purpose: development a classification by structural features and analysis of the application of known of needle threads teke-up mechanisms (MTUNT) sewing machines chain stitch of different types (100, 400, 500, 600 and 800). Methodology includes the main stages of structural and topological analysis, namely: the formation of functional problems, the division of objects (TUNTM) in principle and functional aspect into elements (links, threads teke-up levers, thread guides, thread tension regulator, controllability law and the value of the thread, etc.), topological decomposition of TUNTM and the relationship between them, without delving into their meaningful description, grouping by type and implementation of the type of stitch. Findings are the result of a generalized classification of TUNTM, which takes into account the type of mechanism, belonging to the type of links, the presence of automated control systems and electromechanical devices. In addition, the characteristics of TUNTM are obtained, which are structured into groups in accordance with their use in sewing machines to form certain types of chain stitches. Originality is the structural and topological analysis of TUNTM sewing machines chain stitch and the development of their classification. Practical value of the work lies in the systematization of the known TUNTM, which facilitates the choice of their structure in the design of chain stitch sewing machines.